Clinical Presentation, Risk Factors, and Coronary Angiographic Profile of very Young Adults (≤30 Years) Presenting with First Acute Myocardial Infarction at a Tertiary Care Center Karachi - Rizwan Khan, Javed Khurshed Shaikh, Muhammad Hassan Butt, Iftikhar Ahmed, Ahsan Raza, Tariq Ashraf (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To characterize the clinical demonstration, risk factors, echocardiographic, and coronary angiographic profile of very young individuals presenting with their first AMI at a tertiary care hospital at NICVD Karachi Sindh, Pakistan Background: Rare cases of acute coronary syndrome (ACS) occur in relatively young persons under the age of 30. In Pakistan, <2% of people have experienced an acute myocardial infarction (AMI). When it happens at this young age, ACS has a substantial impact on the patient's psyche, morbidity, and increased financial burden. Single-vessel disease and non-obstructive stenosis are considerably more common in young individuals with ACS on coronary angiography (CAG). Materials and Methods: At the Department of Cardiology NICVD Karachi, this retrospective observational research was carried out. Very young individuals (≤30 years of age) who had their first AMI from 1st January to 30th June 2019 had their medical records gathered and examined. Results: 50 young patients aged ≤30 years old were hospitalized with their first AMI. The majority of the patients were between the ages of 25–30 years. Patients had a mean age of 28.62 ± 2.04 years, and 48 of them (96%) were men. Smoking was the most frequent risk factor for CAD, accounting for 54% of cases in individuals under the age of 30. One patient presented with a complete heart block and a temporary pacemaker was inserted as a lifesaving measure. STEMI (78%) was more common as compared to NSTEMI (22%). The mean left ventricular ejection fraction was 41.4±7.6%. The single-vessel disease was the most prevalent (60%) finding. The most common culprit vessel was the LAD artery (40%) followed by the RCA (14%). The double-vessel disease was seen in 22% of individuals and the most common combination of vessels was LAD and RCA (14%). Conclusion: When compared to older patients, very young individuals showed less severe CAD, which is probably because their coronary arteries had less atherosclerosis. Smoking and dyslipidemia are the most avoidable risk factors in Pakistan's youthful population. Primary prevention, such as public awareness campaigns about the dangers of smoking, poor eating habits, and sedentary lifestyles, may assist to avert the emergence of cardiac issues in later life. Keywords: Acute coronary syndrome, coronary artery disease, smoking, young adults